Investigação dos padrões globais de movimento das manchas solares associadas a região ativa NOAA 12673 - Castanheira, Matheus Leal (2022)
Sunspots are magnetic structures that appear as dark regions in the solar surface. In this work we determine the velocity field responsible for the dynamics of a sunspot group associated with active region NOAA 12673, during its passage close to the disk center, and investigate its properties. The obtained velocity field shows that the dynamics of the sunspots associated to active region NOAA 12673 consists of a main structure, which stays practically at the same position during the investigated period, and of fragments that move around the main structure like a fluid around an obstacle. During their evolution the fragments coalesce forming larger structures. The velocity field shows a complex structure with the presence of a large number of critical points. This number increases during the analysed period indicating that the velocity field becomes more and more complex. We also identify the presence of attracting and repelling vortexes associated to critical points of the type focus. An analysis of the rotation sense indicated that there is no preference for clockwise or counter-clockwise rotation. The velocity field investigated in this work may have a significant contribution to the activity of NOAA 12673, one of the most flare producing active region of the solar cycle 24.